2001
DOI: 10.1080/01612840152053110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Substance Abuse Treatment Completion for Women

Abstract: Substance abuse by women is considered an individual pathology, and the larger social processes of recovery are seldom explored. This research study examined social factors that influenced completion of an outpatient women-centered substance abuse treatment program. The treatment records of a group of 15 women who completed the program were compared with a group who did not complete the program. More completers had previous life successes in the areas of education, job skills, and employment history. Completer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 18 publications
3
47
0
1
Order By: Relevance
“…While mixed-gender samples allow for examination of gender-specific predictors of retention, a number of studies have examined predictors of retention among women-only samples (Brown et al, 1995;Davis, 1994;Hughes et al, 1995;Huselid et al, 1999;Haller and Miles, 2004;Kelly et al, 2001;Knight et al, 1999;Loneck et al, 1997;Stahler et al, 2005;Szuster et al, 1996). Research using women-only samples has found associations between certain patient characteristics (e.g., psychological function, personal stability and social support, levels of anger, treatment beliefs, and referral source) and rates of retention and completion.…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
See 1 more Smart Citation
“…While mixed-gender samples allow for examination of gender-specific predictors of retention, a number of studies have examined predictors of retention among women-only samples (Brown et al, 1995;Davis, 1994;Hughes et al, 1995;Huselid et al, 1999;Haller and Miles, 2004;Kelly et al, 2001;Knight et al, 1999;Loneck et al, 1997;Stahler et al, 2005;Szuster et al, 1996). Research using women-only samples has found associations between certain patient characteristics (e.g., psychological function, personal stability and social support, levels of anger, treatment beliefs, and referral source) and rates of retention and completion.…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
“…Research using women-only samples has found associations between certain patient characteristics (e.g., psychological function, personal stability and social support, levels of anger, treatment beliefs, and referral source) and rates of retention and completion. Kelly et al (2001) reported that having fewer children, higher levels of personal stability, less involvement with child protective services, and fewer family problems predicted treatment completion among 34 women in a women-centered program. Brown et al (1995) found that among 203 women in residential treatment, those with a high level of burden (measured by the number and severity of psychological, cognitive, health, and substance abuse problems) had lower retention rates than those with lower levels of burden.…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] The findings for gender, substance use severity, current legal status, and psychiatric status have been mixed, with no clear indications of commonality of influence across classes of substances used or treatment modality. 1,7,[11][12][13][14][15][16][17][18][19] The influence of psychiatric status on attrition is especially complex, with findings varying within and across diagnostic categories, time of measurement (lifetime vs current disorder), and gender.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to studies~Broome, Flynn, & Simpson, 1999;Haller, Miles, & Dawson, 2002;Kelly et al, 2001! that reported that individuals with more complex psychiatric and addiction presentations have shorter lengths of stay in treatment, we found no association between baseline severity of symptoms and treatment retention.…”
Section: Note For Tables 3 4 Andmentioning
confidence: 71%